A victimological investigation of farm attacks with specific reference to farmers’ perceptions of their susceptibility, the consequences of attacks for farmers and the coping strategies applied by them after victimisation - Davis, Linda (University of Pretoria, 2013)
Dissertation (MA)--University of Pretoria, 2008.